Compare the Effectiveness of Weight Bearing Exercises and Plyometric Training Improve Joint Position Sense in Osteoarthritis Knee Subjects. - Jeevitha D.; Kotteeswaran K. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: This study was designed to compare the effectiveness of weight bearing exercises and plyometric training to improve joint position sense in osteoarthritis knee subjects. Purpose: To compare the effectiveness of weight bearing exercises and plyometric training improve joint position sense in osteoarthritis knee subjects. Materials and Methods: A total 196 subjects with OA knee were taken from the sri murugan physiotherapy pain and rehabilitation centre-kanchipuram. The subjects are selected based on the inclusion and exclusion criteria.196 subjects were divided into 2 groups. Group A contains 98 subjects received weight bearing exercises and group B contains 98 subjects received plyometric exercises. Both the groups commonly received the IFT. All subjects underwent pre-test measurement with (KOOS) and the same repeated for post-test at the end of 4 weeks. The intervention was given for 4 weeks. The entire study process was conducted from November 2022 to April 2023. Results: The pre-test and post-test were analysed, according to statistical analysis weight bearing exercise group were effective in decreasing the pain score and improved functional outcome with p value <0.0001. Conclusion: This study concluded that weight bearing exercises has high impact in improving the joint position sense and functional outcome in OA knee subjects.